The Monitoring and Evaluation System of the Millennium Villages Project-Potou/Senegal: Close Look at the Mid-term Evaluation Report - Kinda, Ousséni (Consilience, 2013)
This paper explores the monitoring and evaluation system of the Millennium Villages Project in Potou, rural Senegal. It specifically focuses on the first evaluation report undertaken in 2009 after three years of intervention to assess the impacts of the project on communities in Potou. Theory of change, causal attribution, scaling-up, use of evaluation, and learning are the key issues that are addressed throughout the paper. Interviews with beneficiaries and project staff as well as the analysis of the project’s evaluation report revealed that the project has created many positive impacts in the communities of Potou. However, unintended negative results have been observed in the sectors of education, health, and agriculture. Given the weaknesses that have been identified in the evaluation method, this paper suggests some strategies to strengthen the methodology of future evaluations, thus allowing for distinct attribution of the impacts to the project.